PENGARUH DURASI KONTAK LARUTAN IRIGASI EKSTRAK BUAH MAHKOTA DEWA (Phaleria macrocarpa) TERHADAP LUAS PENETRASI KE DINDING DENTIN GIGI SALURAN AKAR (Kajian In Vitro) - , RAHMAT MARWANTO; , drg. H. Dedy Kusuma Yulianto., M.Biotech. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Root canal treatment is a treatment to preserve the teeth in the oral cavity. The failure of this treatment is often caused by the bacteria which attached to the walls of the dentin, and also the presence of smear layer. The complexity of the anatomy of the tooth requiring irrigation solution to improve the cleaning of the root canal. An ideal irrigation solution requires an ability to penetrate into the dentin walls. The aim of this study was to determine the effect of the contact duration of Phaleria Macrocarpa as the irrigation solution towards extensive penetration into the dentin wall. This research used 18 mandibular second premolars which cut on the coronal section and the apical third. Subjects were divided into groups of irrigation solution extracts Phaleria macrocarpa and NaOCl each of 9 subjects. Each group were divided into 3 sub-groups each of 3 subjects. Sub-group I were irrigated for 3 minutes, sub-group II for 5 minutes, sub-group III for 7 minutes. Each group of subject were divided into 3 groups. Group I were irrigated for 3 minutes, 5 minutes in group II and group III for 7 minutes. The subjects were tested the ability of penetration with a broad viewing area of penetration into root canal wall dentin. Each subject was cut into 3 segments of upper, middle, and bottom with a thickness of 1 mm, and were captured with a camera macrodigital then processed with AxioVision software and digital imaging. The data were analyzed using Manova test and LSD test followed by the 95% confidence interval (P<0.05). Manova test result showed a significant effect of contact duration of the Phaleria macrocarpa extracts irrigation solution NaOCl against extensive penetration to the root canal dentin walls (p<0.05). LSD test result showed a significant difference between the duration of contact 3 minutes, 5 minutes, and 7 minutes of irrigation solution Phaleria macrocarpa extract with a solution of NaOCl (p<0.05). In conclusion, contact duration of Phaleria Macrocarpa extracts irrigation solution affect the extensive of penetration to the tooth root canal dentin walls.